(untitled) (Iter, 2022)
The relevance of the notion of "beauty " in the socratic-platonic tradition is an nncontested topic. However. how can u e describe objects. events. discourses as beautiful without knowirtg what "beauty " means? In this paper. I revise Plato s early reflections on beauty without considering Plato s later w orks in which the concept is just used rather than defined. Initially Plato s notion of "beauty " is unresolved and everyday language. as exemplifted by Hippias. is used to describe concrete situations. But later. Plato follows Sócrates’ definition as an effort to find a common notion of the concept. Finally. Plato s notion of "beauty " is transposed to the notion of idea.